Public/Private R&D nexus - Deborah Cox; Dimitri Gagliardi (European Commission, Joint Research Centre (JRC), 2009)
The public-private nexus is a complex interface where policies and infrastructure influence management decisions about R&D investments and innovation opportunities. The interface is continuously evolving and conditions vary from country to country and industry to industry. Technological and market change and industry restructuring introduce new management options to decision makers in established and new entrant companies. Easier access to information and expertise stimulates new ways of working between companies and with other organisations and makes the public-private nexus an international or supranational issue and not just a regional or national concern. Finance and projects can be moved internationally via multinational corporations (MNCs) and global supply-chain networks, and knowledge can be accessed and exploited internationally. Some public-private nexus challenges may, therefore, be outside the scope of policy intervention because they transcend traditional boundaries. There are some problems related to the public-private nexus which have been studied inconclusively for many years and where the framework for asking questions has now changed. In particular is the question of public investments `crowding out' private investments. The contexts in which this phenomenon might occur are becoming more complicated and the distinctions between the public sector and private sector are becoming less clear as a result of partnerships and open or collaborative R&D being devised. The conceptual understanding of these contexts and how best to manage them is increasing via an ongoing analysis of innovation systems and processes. There is no single optimum answer or `one size fits all' solution but rather a need for deeper understanding of the nexus and a practical framework for adapting policy proposals. In addition the effects of policy mix and inherited situations rather than individual or isolated policy initiatives need to be considered. For example, Enzing et al. (2004) contradict the proposition that countries with dedicated biotechnology policy instruments show better commercialisation performance in biotechnology than countries without such instruments. Instead, success is more likely to be determined by the systemic character of public policies that address all elements of the innovation system, including instruments that stimulate the life sciences knowledge base and its commercialisation. The extent to which the public-private nexus might modify incentives for R&D and innovation investment and the extent to which it facilitates support and entrepreneurial inspiration will depend partly on the relative significance of small and medium-sized enterprises and large companies, as industry leaders within an economy, and according to the knowledge intensity of the industries represented. Individuals' skills, levels of education and a propensity to pursue relevant careers in science, technology and innovation will be important. In addition the availability, quality and reputation of R&D facilities and universities' research capabilities will determine the scope for change. This document discusses certain aspects of the public-private nexus of R&D.
Keywords: O33; 330; public-private nexus of R&D; R&D incentives